The relationship between social media fatigue and online trolling behavior among college students: the mediating roles of relative deprivation and hostile attribution bias - Huang, Lexin; Chen, Liangkun; Ma, Suwei (Frontiers in Psychology, 2025)
Based on the General Aggression Model (GAM), this study explores the relationship between social media fatigue and online trolling behavior among Chinese college students, focusing on the mediating roles of relative deprivation and hostile attribution bias as key affective and cognitive mechanisms proposed by GAM. Using a cross-sectional survey design, data were collected from 349 college students from Guangdong via an online questionnaire. Key variables, including social media fatigue, relative deprivation, and hostile attribution bias, were measured using validated scales: the SNS Fatigue Questionnaire, the Personal Relative Deprivation Scale, the Word Sentence Association Paradigm for Hostility, and the revised Global Assessment of Internet Trolling. Structural equation modeling (SEM) was employed to test the hypothesized relationships and mediating effects. The results indicate that social media fatigue is positively associated with online trolling behavior. Furthermore, relative deprivation and hostile attribution bias serve as significant mediating mechanisms in this relationship, forming a chain mediation model. These findings suggest that when users experience social media fatigue, they may feel deprived relative to others, which can lead to a hostile interpretation of others’ behaviors, thereby increasing the likelihood of engaging in trolling. The study highlights the importance of understanding psychological factors that contribute to negative online behaviors and offers insights into potential intervention strategies to mitigate such behaviors by addressing the underlying psychological mechanisms.